THE PAINTINGS OF ILYA GLAZUNOV THROUGH THE PRISM OF THE METHODOLOGIES OF SERGEI EISENSTEIN AND LEV VYGOTSKY / ЖИВОПИСЬ ИЛЬИ ГЛАЗУНОВА СКВОЗЬ ПРИЗМУ МЕТОДОЛОГИИ СЕРГЕЯ ЭЙЗЕНШТЕЙНА И ЛЬВА ВЫГОТСКОГО - KONSON G.R. / КОНСОН Г.Р. (Наука телевидения)
In the present article the attempt is made for the first time to apply the methodologies of Sergei Eisenstein and Lev Vygostsky to analysis of the paintings of Ilya Glazunov as well as some of his contemporaries. The attention of the researcher is focused on the phenomenon of the character suite discovered by Einsenstein in drawings as “pure motion of the run of montage thought.” The present phenomenon was focused on disclosing one and the same emotion in its various gradations. Its versatile discovery is also aided by analysis of the other principles of movie montage the manifestation of which is revealed by the author of the article in painting as well: the parallel, associative and intellectual. For the aim of revealing the essence of the examined works of pictorial art the article makes use of a method, correlating with Eisenstein’s, formulated by Soviet scientist Lev Vygotsky, who researched in literature the psychology of inner conflict of images on the basis of the contrariety of the plot and the storyline. The convergence of the mentioned intellectual paths of learning about the paintings of Glazunov and his contemporaries creates the possibility of systematic perfection of “multiple-point entering” into the artistic image, which makes it possible to elucidate the meaning of the authorial conceptions in pictorial art, including those paintings by Glazunov which by their worldview content and image-related compositional solution arouse impassioned critical reactions.